Does the Entry Point of Proximal Femoral Nail Antirotation Affect the Malalignment of Intertrochanteric Fracture? A Cadaveric Study - Jiamton, Chittawee; Nimmankiatkul, Nonpawit; Rungchamrassopa, Pongsakorn; Kanchanatawan, Wichan; Chiarapatanakom, Pariyut; Kongcharoensombat, Wirat (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Proximal femoral nailing (PFN) is a reliable and common procedure for treating intertrochanteric fractures. The optimal entry point is considered a critical step in avoiding malreduction. This study investigated the effects of various entry points on fracture displacement and force reduction. Methods: Twenty-four cadaveric femurs were randomly categorized into three groups: the greater trochanter (GT) tip, medial to the GT tip, and lateral to the GT tip. Each intact femur was provisionally stabilized using a ring external fixator. The entry point was identified and reamed to accommodate the nail insertion. After osteotomy was performed to simulate an A1-type fracture, the PFN was inserted. Digital calipers were used to measure horizontal fracture displacements. The force required to reduce displaced fractures to the anatomical position was measured using a digital force gauge. Fluoroscopic images were recorded to assess changes in the neck-shaft angle. Results: The lateral entry group showed significantly displaced fractures in the coronal plane, whereas the medial and tip entry groups were insignificant. Displacement in the sagittal plane was not significantly different between the groups. The lateral entry group showed significantly irreducible displaced fractures compared with the other groups. After nail insertion, the changes in the neck-shaft angle were 0.77° varus, 3.66° valgus, and 3.16° varus in the tip, medial, and lateral entry groups, respectively. The degree of neck-shaft angle change demonstrated significant differences between the groups. Conclusions: The lateral entry point of PFNA tends to displace reduced fractures, resulting in malalignment and irreducibility. Lateral entry points should be avoided to prevent surgery-related complications.